Is Fair Trade 'Fair'? A Study of Handmade Paper Producers in Nepal. (July 2015) - Kharel, Arjun; Middendorf, Gerad
Examines the perceptions, understanding, and practices of actors engaged in producing and marketing fair trade handmade paper products. The study also assesses the impact of fair trade affiliation on the socio-economic conditions of producers and workers. Primary data were gathered through interviews and participant observation at three paper companies in the Kathmandu area, two of which are fair trade affiliated and one non-affiliated. Secondary data were gathered through available statistics and other documentation. Findings indicate that organisations affiliate with fair trade networks primarily to increase sales, and indeed, affiliation seemed to have positive impacts on sales. Workers were found to lack an understanding of fair trade due to lack of opportunities to participate in decision making, high levels of illiteracy, and because management did not consider worker awareness of fair trade as significant. Worker awareness notwithstanding, company participation in fair trade was positively related to improved socio-economic conditions of workers.